Mendidik Anak Usia Dini Berdasarkan Teori Albert Bandura: Penerapan “Habitus“ Perilaku - Pasiska, Pasiska (STAI Bumi Silampari, 2024)
The writing is aimed at knowing the method of educating children in accordance with the Hadith the Messenger of Allah based on theory of Albert Bandura. With a focus toward early childhood, by applying behavioral conditioning taught parents, who act as a